1991
DOI: 10.1111/j.1559-1816.1991.tb00467.x
|View full text |Cite
|
Sign up to set email alerts
|

The Mediational Role of Perceived Competence in Psychological Adjustment to Rheumatoid Arthritis1

Abstract: Chronic illnesses such as rheumatoid arthritis (RA) have been linked to poor psychological adjustment, although individual differences in this relationship have been observed. This study examines the role of perceived competence as a mediator between RA and adjustment. Persons with RA (N= 208) were surveyed three times at 6‐month intervals concerning several potential antecedents of adjustment (pain, psychosocial impairment, social support, and control beliefs), self‐perceived level of competence, and level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
0
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 59 publications
6
53
0
1
Order By: Relevance
“…with a high internal health locus of control and a low orientation to chance) evaluate haemophilia äs less demanding. This corresponds with studies among patients with rheumatoid arthritis (Smith et al, 1991;Smith and Wallston, 1992), in which a generalized sense of competence contributed to an increased life satisfaction and buffered against depressive Symptoms. From other studies it also appeared that patients who strongly believe that they must hold back from domg what they want are more prone to poor psychological adjustment (Turner et a/., 1987;Bombardier et al, 1990).…”
Section: Interpretation and Implicationssupporting
confidence: 85%
See 1 more Smart Citation
“…with a high internal health locus of control and a low orientation to chance) evaluate haemophilia äs less demanding. This corresponds with studies among patients with rheumatoid arthritis (Smith et al, 1991;Smith and Wallston, 1992), in which a generalized sense of competence contributed to an increased life satisfaction and buffered against depressive Symptoms. From other studies it also appeared that patients who strongly believe that they must hold back from domg what they want are more prone to poor psychological adjustment (Turner et a/., 1987;Bombardier et al, 1990).…”
Section: Interpretation and Implicationssupporting
confidence: 85%
“…A sense of control or a feeling of competence, low levels of affective traits and dispositional optimism are all reported to favour well-being (e.g. Weinberger et al, 1990;Smith et al, 1991;Schwarzer, 1994). Social support has been hypothesized to benefit well-being directly äs well äs indirectly by acting äs a mediator or a buffer in coping with stress or illness (Lazarus and Folkman, 1984;Cohen and Wills, 1985;Schulz and Decker, 1985).…”
Section: ( Onceptual Frameworkmentioning
confidence: 99%
“…One explanation might be that depressed people receive more instrumental support because they arouse sympathy. Others argue that receiving considerable instrumental support causes feelings of helplessness or dependency, both of which may cause depression (Penning & Strain, 1994; T. W. Smith, Christensen, Peck, & Ward, 1994). In diabetes mellitus, this association was most obvious.…”
Section: Discussionmentioning
confidence: 97%
“…Dekker, Boot, van der Woude & Bijilsma, 1992, Summers, Haley, Reveille & Alarcon, 1988. Smith, Dobbins and Wallston (1991) found that despite there being a relationship between pain and depression, when pain is controlled for, there is still considerable variation in ILLNESS REPRESENTATIONS, COPING AND ILLNESS OUTCOME 5 psychological adjustment to rheumatoid arthritis -as with similar levels of pain some do better than others.Within the field of rheumatoid arthritis very few studies have examined the basic elements of the self-regulatory model together-that is, illness representations, coping strategies, outcome appraisals -and related these to each other as well as illness outcome measures. Studies have tended to focus on one or two aspects of the model (e.g.…”
mentioning
confidence: 99%
“…Dekker, Boot, van der Woude & Bijilsma, 1992, Summers, Haley, Reveille & Alarcon, 1988. Smith, Dobbins and Wallston (1991) found that despite there being a relationship between pain and depression, when pain is controlled for, there is still considerable variation in ILLNESS REPRESENTATIONS, COPING AND ILLNESS OUTCOME 5 psychological adjustment to rheumatoid arthritis -as with similar levels of pain some do better than others.…”
mentioning
confidence: 99%